Dr. Jonathan - Churchill, Winston, 1871-1947 (Salt Lake City, UT : Project Gutenberg, 2004)
"Dr. Jonathan" by Winston Churchill is a play in three acts written during the tumultuous period of the First World War. It explores themes of class struggle, economic freedom, and human rights, particularly in the context of the labor issues exacerbated by the war. The central characters include George Pindar, the son of a factory owner, and Dr. Jonathan Pindar, his cousin, who has returned to their New England hometown to grapple with the implications of self-determination and labor rights amidst societal change. The opening of the play sets the stage in the library of Asher Pindar$1 (Bs home, where father and son engage in a conversation about the impending war and the state of labor relations. As George prepares to leave for the front, tensions arise over the management of the family business and the dissatisfaction among workers, particularly regarding union recognition. The arrival of Dr. Jonathan, a new character with a scientific background, introduces a different perspective on the conflict, emphasizing the importance of economic democracy in achieving true political freedom. Through witty dialogue and the personal dilemmas faced by the characters, the opening portion lays down the foundation for exploring the larger social issues at play during this critical moment in history. (This is an automatically generated summary.)s
Release date is 2004-10-19
Produced by David Widger
Keywords: World War, 1914-1918 -- Drama; Veterans -- United States -- Drama; Mills and mill-work -- Management -- Drama; New England -- Drama